Cell membrane status and cations in essential and malignant hypertension. - Touyz, Rhian (My University, 1991)
Abnormal cell membrane function and altered cellular cation homeostasis have been implicated in the pathogenesis of essential hypertension. The role of these factors in the aetiology of malignant hypertension is unknown. (Abbreviation abstract)
A thesis submitted to the Faculty of Medicine. University of the Witwatersrand. Johannesburg, for the Degree of Doctor of Philosophy
Keywords: Hypertension.; Hypertension, Malignant.; Cell Membrane.